Enhancing postpartum hemorrhage training by integrating case-problem based learning with simulation: a quasi experimental study - Yang, Yike; Guo, Zhichao; Guo, Xiaoyue; Zhao, Yangyu (Journal of obstetrics and gynaecology, 2025)
Postpartum haemorrhage (PPH) is the leading cause of maternal mortality worldwide, and effective training in PPH rescue techniques is crucial. This study aims to evaluate the effectiveness of combining case-based learning (CBL) and problem-based learning (PBL) with simulation teaching methods in improving midwifery trainees' technical proficiency in managing PPH. This quasi-experimental study involved 76 trainees who received PPH training at Peking University Third Hospital from March to July 2023. They were divided into two groups: the control group ( = 50) followed traditional simulation training methods, and the research group ( = 26) used a combination of CBL-PBL and scenario simulation. After the training, all participants completed a theoretical examination and questionnaire to assess their satisfaction with the program and self-assessment of clinical management skills in PPH. Statistical analysis was performed using unpaired t-tests and chi-square tests to compare the groups. The combination of CBL-PBL and scenario simulation was highly satisfactory compared to traditional simulation training, significantly enhancing self-assessed skills in clinical thinking (100% vs. 61.8%, = .03), operant skills related to PPH (100% vs. 57.4%, < .01), relevant knowledge pertaining to PPH (100% vs. 58.7%, < .01), and management abilities (97.1% vs. 39%, < .01) among midwifery trainees in the research group, who also scored significantly higher on post-training assessments of PPH knowledge than control groups(91.7 ± 6.0 vs 76.0 ± 7.1, < .01). A majority of trainees expressed a preference for regular simulation exercises (98.7%) and detailed discussions on PPH cases (93.4%) in future training sessions. Combining CBL-PBL with simulation practice is a more effective teaching method for PPH management training in maternity staffs with a certain level of clinical experience, compared to traditional methods. Future studies should explore the implementation of regular PPH rescue skill training in real clinical settings to support these findings.